2018
DOI: 10.1002/cam4.1696
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed lncRNAs and mRNAs identified by NGS analysis in colorectal cancer patients

Abstract: Long noncoding RNAs (lncRNAs) play an important role in gene regulation, but their impact on the pathogenesis of colorectal cancer and the biological function of cancer cells is unclear. In this study, we used next‐generation sequencing to study the differences in the expression profiles of lncRNAs and mRNAs in colorectal cancer tissues. We analyzed the differentially expressed genes by Gene Ontology/Kyoto Encyclopedia of Genes and Genomes (GO/KEGG) enrichment and predicted new lncRNA functions. Our results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…Feodorova et al revealed that NOTUM, TCN1, MACC1, YKL40, GPC3, AXIN2, and IL6 are significantly upregulated in CRC and have roles in tumour invasion and metastasis 11 . Our previous next-generation sequencing (NGS) results verified that TCN1 is one of the top five overexpressed mRNAs in CRC 12 . Taken together, these findings indicate that TCN1 is a CRC-related gene that requires further study.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Feodorova et al revealed that NOTUM, TCN1, MACC1, YKL40, GPC3, AXIN2, and IL6 are significantly upregulated in CRC and have roles in tumour invasion and metastasis 11 . Our previous next-generation sequencing (NGS) results verified that TCN1 is one of the top five overexpressed mRNAs in CRC 12 . Taken together, these findings indicate that TCN1 is a CRC-related gene that requires further study.…”
mentioning
confidence: 64%
“…We hypothesized that TCN1 might have a role in colon cancer. The NGS results in CRC revealed that TCN1 ranked as the second most upregulated mRNA 12 . Bioinformatic analysis based on the COAD data set verified that TCN1 was indeed overexpressed in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…FIRRE upregulation is associated with poor OS time in diffuse large B-cell lymphoma, CRC and HNSCC (67). However, FIRRE upregulation is also associated with significantly improved OS time in CRC (68). The present study revealed that FIRRE was upregulated in numerous types of cancer, possibly indicating that this lncRNA behaves differently under different circumstances.…”
Section: Discussionmentioning
confidence: 50%
“…Results shown are sorted from highest to lowest percent abundance in the colon cancer cohort. D. Fold change of top upregulated and downregulated human genes(Li et al, 2018) between CRC and matched normal samples as found in this study through MetaFunc.…”
mentioning
confidence: 60%
“…From these, we found all the top 5 upregulated and top 5 downregulated genes as reported in the source publication (Li et al, 2018). Figure 2D shows their fold change as found through MetaFunc.…”
Section: Hostmentioning
confidence: 93%